Development of Cultural Tourism Potential to Enhance the Local Economy in Ohoi Faan, Southeast Maluku Regency - Yonas Daminaus Fangohoi; Ida I Dewa Ayu Raka Susanty; Jamaludin Kabalmay; Anggiat M. Manullang; Rahma Gusmawati Tammu; Michael Gerits Kriswanto Remetwa (Sean Institute, 2025)
Ohoi Faan in Southeast Maluku Regency has a rich potential for cultural tourism, with various cultural activities that are still actively practiced by the local community as a traditional royal village. This study explores the cultural tourism potential of Ohoi Faan in the Kei Islands, an area rich in cultural heritage and history. The main goal is to understand how developing this potential can contribute to strengthening the local economy. Using a qualitative descriptive approach—through interviews, participatory observations, and document reviews—the research highlights several cultural sites, such as traditional houses, ancient wells, royal tombs, and Japanese bunkers, which could attract visitors. Local cultural festivals like Meti Kei, along with traditional crafts, also add to the area's appeal. Despite facing challenges such as limited infrastructure and minimal government support, the local community shows strong commitment to preserving its cultural identity. This is evident in their collaborative efforts with various stakeholders. Developing cultural tourism in Ohoi Faan offers promising opportunities—not only for creating jobs and boosting small businesses (SMEs) but also for promoting sustainable economic growth without compromising the region’s cultural values.